2006
DOI: 10.1212/01.wnl.0000249185.78359.06
|View full text |Cite
|
Sign up to set email alerts
|

CNS involvement in hereditary neuropathy with pressure palsies (HNPP)

Abstract: We assessed seven patients with hereditary neuropathy with liability to pressure palsies (HNPP) with 16 electrophysiological tests and cranial MRI for CNS abnormalities. Mean latencies differed between patients with HNPP and controls for the blink reflex, the jaw-opening reflex, and acoustic evoked potentials. MRI abnormalities were observed in four patients. Our study suggests subclinical but functionally relevant CNS myelin damage in HNPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
1
13
2
Order By: Relevance
“…Of note, although PMP22 is a known peripheral myelin protein, it has been shown that PMP22 is expressed in the CNS (Ohsawa et al 2006). Furthermore, neurological disorders caused by PMP22 duplication has been reported to have CNS phenotype (Tackenberg et al 2006), consistent with a role for PMP22 in CNS. Furthermore, other CNVs including myelin/oligodendrocyte related genes have been reported including RTN4R , (Kirov et al 2009) and LINGO-1 (Ikeda et al 2009).…”
Section: Background: Oligodendrocyte/myelin Dysfunction In Schizopsupporting
confidence: 58%
“…Of note, although PMP22 is a known peripheral myelin protein, it has been shown that PMP22 is expressed in the CNS (Ohsawa et al 2006). Furthermore, neurological disorders caused by PMP22 duplication has been reported to have CNS phenotype (Tackenberg et al 2006), consistent with a role for PMP22 in CNS. Furthermore, other CNVs including myelin/oligodendrocyte related genes have been reported including RTN4R , (Kirov et al 2009) and LINGO-1 (Ikeda et al 2009).…”
Section: Background: Oligodendrocyte/myelin Dysfunction In Schizopsupporting
confidence: 58%
“…His brain MRI was normal. To date only a few cases of central nervous system involvement have been described in HNPP …”
Section: Discussionmentioning
confidence: 99%
“…To date only a few cases of central nervous system involvement have been described in HNPP. [18][19][20] Authors of guidelines for diagnosis of HNPP recognize that electrophysiological criteria are met by the patients, even those who are asymptomatic and are older than age 15. 11 Our study stresses the role of electrophysiological testing of the parents of probands with clinical diagnosis of HNPP.…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system white matter lesions have been reported in isolated patients and in several members of a large family with HNPP [169-171]. A recent report on 15 HNPP patients described central nervous system involvement [60].…”
Section: Pmp22 Deletion - Hereditary Neuropathy With Liability To Prementioning
confidence: 99%